Integrative analysis of transcriptome and lipidome reveals fructose pro-steatosis mechanism in goose fatty liver - Wei, Rongxue; Han, Chunchun; Wei, Shouhai; Teng, Yongqiang; Li, Liang; Liu, Hehe; Hu, Shengqiang; Kang, Bo; Xu, Hengyong (Frontiers in Nutrition, 2023)
To further explore fructose pro-steatosis mechanism, we performed an integrative analysis of liver transcriptome and lipidome, as well as peripheral adipose tissues transcriptome analysis using samples collected from the geese overfed with maize flour (control group) and the geese overfed with maize flour supplementation with 10% fructose (treatment group). Overfeeding period of treatment group was significantly shorter than that of control group (P < 0.05). Dietary supplementation with 10% fructose induced more severe steatosis in goose liver. Compared with control group, treatment group was lower in ceramide level (P < 0.05). The key differentially expressed genes (DEGs) (control group vs treatment group) involved in liver fatty acid biosynthesis and steroid biosynthesis were down-regulated. The conjoint analysis between DEGs and different lipids showed that the fatty acid biosynthesis and steroid biosynthesis were the highest impact scores pathway. In conclusion, fructose expedites the goose liver lipid accumulation maximization during overfeeding.